The politics of the "post-political" contesting the diagnosis. Issue 3 (2nd April 2020) - Meyer, John M.
ABSTRACT: The diagnosis of our present age as "post-political" have become commonplace among political theorists and other scholars. This diagnosis is critiqued here on the grounds that it offers an account of temporality and hegemony that are fundamentally misleading. While these authors' critical stance toward technocratic managerialism is warranted, the post-political diagnosis itself serves to narrow our political imagination and weakening our ability to perceive opportunities for change. Following Sheldon Wolin, a "fugitive" conception of democracy can offer greater insights into the shifting and unpredictable dynamics of politicization and depoliticization. This analysis is advanced with particular attention to the ways the post-political diagnosis plays out with respect to environmental politics, climate change, and arguments that we are now living in the epoch of the Anthropocene.